CORONAVIRUS (COVID-19): LET'S PREVENT NOT PANIC - Mukhtar, Fatima; Mukhtar, Neha (Journal of Ayub Medical College Abbottabad, 2020)
It was on 31st December 2019, that a cluster of pneumonia cases was reported to the World Health Organization (WHO) by China. The initial investigations revealed the cases to be due to a previously unknown never before seen strain of coronavirus. Coronaviruses are a group of viruses, which are normally present among animals such as cows, bats, camels and cats. The disease was officially named COVID-19 by WHO on 11th February 2020. The International Committee on Taxonomy of Viruses named the virus as SARS-CoV-2 due to its resemblance to SARS coronavirus. According to WHO's Situation Report-28 as of 17th February 2020, globally there were 71,429 confirmed cases, which included both laboratories confirmed and clinically diagnosed cases (applicable only to Hubei province of China). Cases are clinically diagnosed based on their signs and symptoms and chest x-rays without laboratory testing. More than 99% of these are in China i.e. 70,635 and 794 are outside China. The cases reported outside of China belong to 25 countries in various regions of WHO: China having the epicenter of the disease bears the greatest brunt, with 1772 deaths. The three deaths outside China have been reported in Philippines, Japan and France. The case fatality rate of COVID-19 ranges between 2-3% A wide spectrum of disease, ranging from mild to severe, has been reported in confirmed cases of COVID-19. Respiratory symptoms, fever, cough, dyspnoea, myalgia, fatigue, breathing difficulties and bilateral lung infiltrates on C.T are common findings. Pakistan so far has not reported any confirmed case of COVID-19. Government is showing its commitment towards the threat of importation. This novel coronavirus, called as a devil by Chinese Prime Minister, Xi Ping is really an enigma. Keywords: Coronavirus, COVID-19, Wuhan, SARS, SARS-CoV-2